FtH-Mediated ROS Dysregulation Promotes CXCL12/CXCR4 Axis Activation and EMT-Like Trans-Differentiation in Erythroleukemia K562 Cells - Chirillo, Roberta; Aversa, Ilenia; Di Vito, Anna; Salatino, Alessandro; Battaglia, Anna Martina; Sacco, Alessandro; Di Sanzo, Maddalena Adriana; Faniello, Maria Concetta; Quaresima, Barbara; Palmieri, Camillo; Biamonte, Flavia; Costanzo, Francesco (Frontiers in Oncology, 2020)
The cell-microenvironment communication is essential for homing of hematopoietic stem cells in stromal niches. Recent evidences support the involvement of epithelial-to-mesenchymal (EMT) process in hematopoietic stem cell homeostasis as well as in leukemia cells invasiveness and migration capability. Here, we demonstrate that the alteration of iron homeostasis and the consequent increase of redox metabolism, mediated by the stable knock down of ferritin heavy chain (FtH), enhances the expression of CXCR4 in K562 erythroleukemia cells, thus promoting CXCL12-mediated motility. Indeed, addition of the CXCR4 receptor antagonist AMD3100 reverts this effect. Upon FtH knock down K562 cells also acquire an “EMT-like” phenotype, characterized by the increase of Snail, Slug and Vimentin with the parallel loss of E-cadherin. By using fibronectin as substrate, the cell adhesion assay further shows a reduction of cell adhesion capability in FtH-silenced K562 cells. Accordingly, confocal microscopy shows that adherent K562 control cells display a variety of protrusions while FtH-silenced K562 cells remain roundish. These phenomena are largely due to the reactive oxygen species (ROS)-mediated up-regulation of HIF-1α/CXCR4 axis which, in turn, promotes the activation of NF-κB and the enhancement of EMT features. These data are confirmed by treatments with either N-acetylcysteine (NAC) or AMD3100 or NF-κB inhibitor IκB-alpha which revert the FtH-silenced K562 invasive phenotype. Overall, our findings demonstrate the existence of a direct relationship among iron metabolism, redox homeostasis and EMT in the hematological malignancies. The effects of FtH dysregulation on CXCR4/CXCL12-mediated K562 cell motility extend the meaning of iron homeostasis in the leukemia cell microenvironment.